THE DESIRE FOR RECOGNITION IN THE CONTEXT OF FRANCIS FUKUYAMA’S UNIVERSAL HISTORY - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Introduction. Francis Fukuyama in his famous book “The End of History and the Last Man” assumes that human history should be considered as the battle of ideologies that reaches its goal in the universalization of Western liberal democracy. Author’s ideas have gained many supporters. At the same time, they were subjected to severe criticism that reflected the important trends of political life and ideological preferences. Leaving aside the criticism based on geopolitical and civilizational confrontation and confusion which confronts Fukuyama’s theory, it should be stated that anthropological aspect of Fukuyama’s theory has vastly evaded philosophical comprehension. Purpose. This article attempts to test Fukuyama’s theory through the lens of philosophical anthropology and analyze human desire for recognition in the context of Fukuyama’s World History. Methodology. The analysis is focused on human desire for recognition as a significant dimension of human nature. The author has used hermeneutical methodology and anthropological integrative approach. Theoretical basis and results. Fukuyama is not satisfied by merely economic interpretation of history emphasizing that human is not simply an economic animal. Economic development fails to explain why people advocate the principles of liberal democracy. The author goes back to Hegel’s non-materialistic view of history based on the struggle for recognition. According to Fukuyama, this deeply rooted human desire for recognition is the great motor of history and cause of tyranny, conflicts, and wars. But at the same time, it also acts as a psychological foundation of many virtues – the spirit of citizenship, courage, and justice. Throughout history, this desire for recognition was not satisfied. Only modern liberal democracy provides universal recognition of all humans ensuring and protecting their rights. Originality. Fukuyama’s concept is important and interesting because it draws attention to the sphere of human values, which essentially influences the basis of personality structure. Unlike traditional liberalism, which focuses on materialism and justice, Fukuyama considers the struggle for recognition, the spiritual search for human dignity and equality (or superiority) the major component of social transformation. Human acts as a central point of political, cultural, economical space: he/she is the creator and the creation. Conclusions. Over time, the concept of Fukuyama has undergone significant changes. Modern civilization has been facing with an acute problem of growing inequality, serious financial crisis, political havoc and military conflicts, migrants and refugees problem. But so far the idea of liberal democracy has no real competitors.